2016
DOI: 10.1007/s00277-016-2634-x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to the prevention of central venous catheter complications: results of 10-year prospective surveillance in pediatric hematology-oncology patients

Abstract: We report our decennial experience with 1161 newly-placed long-term central venous catheters inserted in 919 hematology-oncology patients for a total of 413,901 CVC-days of observation. Most of the CVCs were partially-implanted, open-ended, Broviac-Hickman type of CVC (95 %). One thousand and twenty-four complications were recorded equal to 2.47 per 1000 CVC-days. The frequency of complications per CVC, the rate of episodes per 1000 CVC-days, and removal rate were malfunction/occlusion 42 %, 1.18/1000, and 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
36
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
12
36
1
8
Order By: Relevance
“…This finding was similar to the report by Cesaro et al, who concluded that one of the risk factors of premature CVC removal was age at CVC positioning, less than 6.1 years. 5 Regarding the frequency of bacteremia, it was comparable to the results of literature in the past. [3][4][5]7 Dual-lumen CVC, or Hickman catheter, is the risk factor for CVC-associated bacteremia in this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding was similar to the report by Cesaro et al, who concluded that one of the risk factors of premature CVC removal was age at CVC positioning, less than 6.1 years. 5 Regarding the frequency of bacteremia, it was comparable to the results of literature in the past. [3][4][5]7 Dual-lumen CVC, or Hickman catheter, is the risk factor for CVC-associated bacteremia in this study.…”
Section: Discussionsupporting
confidence: 88%
“…5 Regarding the frequency of bacteremia, it was comparable to the results of literature in the past. [3][4][5]7 Dual-lumen CVC, or Hickman catheter, is the risk factor for CVC-associated bacteremia in this study. Cesaro et al also pointed out this one as one of the risk factors for bacteremia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Unfortunately, catheter‐related complications may lead to additional surgical revision and premature catheter removal, resulting in interruption or prolongation of therapy . The prevalence of adverse events during catheter implantation has been reported to range between 3.1% and 22% . Complications during the dwell period were found to occur in 20.8–40% of cases, with catheter risk (CR) of 0.97–2.47 per 1,000 catheter days at risk (cdr) .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Complications during the dwell period were found to occur in 20.8-40% of cases, with catheter risk (CR) of 0.97-2.47 per 1,000 catheter days at risk (cdr). 4,[7][8][9] Furthermore, there are conflicting data on the percutaneous insertion technique versus surgical venous cut down, as well as the use of ultrasonography and its benefits compared to the landmark technique. [10][11][12][13][14][15] Therefore, the aim of our study was to determine the frequency and type of adverse events during catheter insertion in landmark-guided percutaneous technique as well as longterm complications during the dwell period in this particular patient group.…”
Section: Introductionmentioning
confidence: 99%